Classifying Residential Real Estate Based on Their Exposure to Crime: A Research Agenda - Marques, S.; Ferreira, F.; Meidute-Kavaliauskiene, I. (International Conference on Contemporary Issues in Business, Management and Education, 2017)
Criminality and sense of security in residential areas are always present in the mind of citizens, and directly affect the work of police authorities, real estate agents and society at large. This study proposes the development of a multiple criteria model for the classification of residential areas based on their exposure to crime. By combining cognitive mapping with the Measuring Attractiveness by a Categorical Based Evaluation Technique (MACBETH), we also aim to increase transparency in the classification process of residential real estate, allowing improvement initiatives to be applied and crime rates to be reduced. The major difference between our proposal and the extant literature is the fact that the information collected from criminal, urbanism and real estate experts, who deal with crime adversities on a daily basis, will be analyzed and discussed during presential group meetings, allowing realism to be incorporated into the evaluation mechanism. The current proposal is a research agenda, and results will not yet be presented.